Specific Features of Russian Economy Development on the Current Stage - L. I. Kochurova (Plekhanov Russian University of Economics, 2020)
The article studies the current economic situation in Russia: problems of economy development, the role of stateowned corporations and small and medium business in economy, problems of their interaction and key lines in development in the near future. The structure of domestic product of the country was described, as well as the role of certain industries of business in its formation. The chief goal of state is to re-orientate from resource-mining to resource – processing, which complies with the concept of added value and shall ensure the sustainable development of economic growth. The authors come to the conclusion that only interaction of big, medium and small business in the country can provide certain success in development, that human factor, interest of workers in results of enterprise work can become a decisive factor on the current stage. Key vectors of economy development in Russia have been identified. It was underlined that state must become an important regulator of market processes in the country. Today Russia must choose its future strategy: it can be either an inertial way of neo-liberal reforms and degrading of scientific potential or mobilization of intellectual resources to restructure economy on principles of developed market with the leading role of state.